EGFR-TARGETING PEPTIDE INHIBITS HELA CELL PROLIFERATION: A NOVEL STRATEGY FOR CERVICAL CANCER THERAPY? - Reem Hussin; Danielle Vieira Sobral; Fernanda Ferreira Mendonça; Leonardo Lima Fuscaldi; Luciana Malavota (Hematology, Transfusion and Cell Therapy)
Introduction/Justification: Cervical cancer remains one of the leading causes of cancer-related mortality in women worldwide, with EGFR overexpression contributing to uncontrolled proliferation, resistance to apoptosis, and tumor progression. Despite advances in radiotherapy and chemotherapy, many patients develop resistance, highlighting the urgent need for targeted therapies that can disrupt these oncogenic pathways. Peptide-based drugs represent a promising avenue for precision oncology, offering high specificity, low toxicity, and potential to inhibit key molecular drivers of cancer. This study investigates the YHWYGYTPQNVT peptide, designed to interact with EGFR, and evaluates its effect on proliferation and migration of HeLa cells, a widely used model of cervical cancer. Objectives: This research aims to determine whether the YHWYGYTPQNVT peptide can effectively suppress EGFR-mediated growth signaling in HeLa cells, by analyzing cell proliferation, metabolic activity, and migration, aiming at establishing its potential as a therapeutic alternative to traditional cancer treatments. Materials and Methods: The YHWYGYTPQNVT peptide was synthesized using solid-phase peptide synthesis, purified via HPLC, and confirmed by mass spectrometry. HeLa cells were cultured in DMEM + 10% fetal bovine serum and incubated at 37°C with 5% CO₂. To establish a baseline proliferation rate, HeLa cells were plated at 5 × 104 cells in 6-well plates, and the growth curve was performed in sextuplicate over a 5-days period, with cell counts conducted on days 1, 3 and 5. For the experimental group, cells were treated with YHWYGYTPQNVT (80 µmol/mL). Statistical analysis was conducted using GraphPad Prism, with significance set at p ≤ 0.05. Results: The YHWYGYTPQNVT peptide was synthesized efficiently with yield of approximately 45%. Chromatographic analyzes obtained by HPLC and mass spectrometry confirmed that the entire synthesis, cleavage, and purification process of peptides were performed efficiently. Control group displayed an aggressive proliferation rate with an exponential growth, reaching ∼96.8 × 10⁴ cells, consistent with the known oncogenic potential of HeLa cells. In contrast, the peptide-treated group showed a significant reduction in proliferation, with final cell counts averaging 61.5 × 10⁴ cells - corresponding to a 25.5% decrease compared to untreated cells. Conclusion: Our findings highlight YHWYGYTPQNVT as a promising EGFR-targeting agent capable of reducing cervical cancer cell proliferation. By directly interfering with EGFR-driven oncogenic pathways, this approach could lay the groundwork for a new class of peptide-based therapeutics in oncology. Further in vivo validation and molecular pathway analysis are necessary to determine its potential clinical application in patients with EGFR-overexpressing cervical tumors.